Bacterial Resistance Pattern to Cephalosporin in Patient with Chronic Osteomyelitis at Dr. Hasan Sadikin General Hospital Bandung - Daniel Christian Fernandez; Ghuna Arioharjo Utoyo; Adhi Kristianto Suganli (Althea Medical Journal, 2016)
Background: Chronic osteomyelitis remains difficult to treat and has a high rate of relapse after apparently succesful treatment. Cephalosporin has been greatly used for the antibiotic intervention for patient with osteomyelitis. The objective of this study was to explore bacterial profile and its microbial resistance pattern of each generation of cephalosporin from patients with chronic osteomyelitis at Dr. Hasan Sadikin General Hospital.Methods: A descriptive study was conducted to 39 medical records from patients with chronic osteomyelitis at Dr. Hasan Sadikin General Hospital that met both inclusion and exclusion criteria. The bacterial pattern and antimicrobial susceptibility test results were obtained from both medical record and laboratory database for five years, during the period of Januari 2009 to December 2014. Data of bacterial species, type of Gram staining, and numbers of resistance isolates to antiobiotic were taken from the collected data and analyzed in form of frequency tabulation and percentages.Results: As high as 43−52% of Staphylococcus aureus isolates were resistant to all generation of cephalosporin. Coagulase-negative Staphylococci and Streptococcus spp. showed resistance to cephalosporin as high as 29% and 67%, respectively. This study also discovered that 5 of 23 Staphylococcus aureus isolates were methicillin-resistant Staphylococcus aureus (MRSA). Klebsiella pneumoniae showed a leading number of resistance pattern for both third and fourth generation of cephalosporin (77%). Enterobacter cloacae showed highly resistance for both first and third generation of cephalosporin, between 57−86%.Conclusions: There is the high resistance of all bacteria to cephalosporin among chronic osteomyelitis patients. [AMJ.2016;3(3):376–81] DOI: 10.15850/amj.v3n3.883